2014
DOI: 10.2172/1166037
|View full text |Cite
|
Sign up to set email alerts
|

NEET In-Pile Ultrasonic Sensor Enablement-Final Report

Abstract: Several programs funded by the Department of Energy Office of Nuclear Energy (DOE-NE), such as the Fuel Cycle Research and Development, Advanced Reactor Concepts, Light Water Reactor Sustainability, and Next Generation Nuclear Plant programs, are investigating new fuels and materials for advanced and existing reactors. A key objective of such programs is to understand the performance of these fuels and materials during irradiation. The Nuclear Energy Enabling Technology (NEET) Advanced Sensors and Instrumentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Acoustic impedance can be calculated as follows [7]: Z=ρcA where ρ denotes material density, c indicates the velocity of sound, and A is the cross-sectional area of the acoustic waveguide. Based on ultrasonic impedance equation, we can deduce the ultrasonic reflection coefficient as follows [21,22]: R=Z2Z1Z2+Z1…”
Section: Ultrasonic Thermometry Requirement and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic impedance can be calculated as follows [7]: Z=ρcA where ρ denotes material density, c indicates the velocity of sound, and A is the cross-sectional area of the acoustic waveguide. Based on ultrasonic impedance equation, we can deduce the ultrasonic reflection coefficient as follows [21,22]: R=Z2Z1Z2+Z1…”
Section: Ultrasonic Thermometry Requirement and Developmentmentioning
confidence: 99%
“…In 2002, the Korea Atomic Energy Research Institute (Kil-MO Koo) used ultrasonic thermometry to measure core temperature in LAVA (Lower-Plenum Arrested Vessel Attack) at 2200 °C [5]. In 2010, the Idaho National Laboratory tested an improved, ultrasonic in-pile sensor for temperature detection during irradiation testing [6,7]. Experiments showed that UO 2 melting with an ultrasonic sensor embedded in a molten pool has a temperature near 3133 K, which is well in accordance with the expected value of 3123 K [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The major difference is magnetostrictive materials are actuated using coils and a magnetic field instead of a voltage applied to electrodes. This type of ultrasonic thermometer is being looked at by the INL for nuclear reactors due to its small size and ability to withstand high temperatures [2]. The small diameter wire also allows for dispersion of ultrasonic waves to be avoided [2].…”
Section: Figure 17mentioning
confidence: 99%
“…This type of ultrasonic thermometer is being looked at by the INL for nuclear reactors due to its small size and ability to withstand high temperatures [2]. The small diameter wire also allows for dispersion of ultrasonic waves to be avoided [2]. INL tests have shown these sensors have increased accuracy when compared to other temperature sensing methods currently available [2].…”
Section: Figure 17mentioning
confidence: 99%
See 1 more Smart Citation